Tremaine's true love ebook - Burrowes, Grace (True Gentlemen, 2015)
A 2016 RITA Finalist for Historical Romanace! New York Times and USA Today bestselling author Grace Burrowes introduces a brand new gorgeous Regency Romance series featuring the Haddonfield ladies and their loves. He's had everything he could ever want...until now Wealthy wool magnate Tremaine St. Michael is half French, half Scottish, and all business. He prowls the world in search of more profits, rarely settling in one place for long. When he meets practical, reserved Lady Nita Haddonfield, he sees an opportunity to mix business with pleasure by making the lady his own. Nita Haddonfield has a meaningful life tending to others, though nobody is dedicated to caring for Nita. She insists the limitations of marriage aren't for her, then Tremaine St. Michael arrives-protective, passionate, and very, very determined to win Nita's heart. True Gentleman series Tremaine's True Love (Book 1) Daniel's True Desire (Book 2) Will's True Wish (Book 3) Grace Burrowes writes heroes you'll never forget. "Exquisite...breathtaking and heartwarming." -Long and Short Reviews for Nicholas "Delightfully different...Burrowes brings to life a deeply moving romance that's sure to be remembered and treasured." -RT Book Reviews Top Pick for Darius